Phenotypic determination of phage susceptibility among multi-drug resistant bacteria isolated from clinical samples of patients of tertiary care centre, Nepal. - Shrestha,Sreska (2021)
ABSTRACT: Introduction: Emergence of multidrug resistant (MDR) strains have become a global threat that has led to increased interest in alternatives. Bacteriophages (BPs) have been studied as a therapeutic agent to treat the bacterial infections for around 100yrs. The lytic bacteriophages can lyse bacteria without attacking on mammalian cells. Thus, it is thought that bacteriophages are significantly safer and better tolerated and utilize the novel mechanisms of action to achieve antibacterial activity. Objective: To isolate and evaluate the in vitro efficacy of bacteriophages against MDR bacteria. Methodology: Bacteriophages were isolated from different environmental sources; river sites, ponds and sewages. Presence of phage was determined by the Double Layer Agar Assay. Concentrations of phage was determined in plaque forming unit per milliliter (PFU/ml) by performing plaque assay and susceptibility test was done by observing their lytic effect on pre identified MDR bacteria. Results: Bacteriophages were obtained from 11 different sources and 52 out of 73 bacteriophages which showed clear lytic property were selected. Majority of the isolated phages had lytic effect on their respective specific MDR with varying degree, mostly high efficacy (+++) showing high specificity. However, CF showed minimum lytic effect even on Citrobacter freundii, indicating narrow spectrum. PR42 and PR44 had wider spectrum of lytic effect on majority of the MDR isolates. Overall, phages specific for Gram Negative Bacilli (GNB) showed lytic effect predominantly on GNB whereas phages specific for Gram Positive Cocci (GPC) showed lytic effect predominantly on GPC. Conclusion: Phage therapy can be a promising alternative to antimicrobial therapy for treatment of patients infected with MDR bacteria, which are usually severe infections. Keywords: bacteriophage, MDR bacteria, Bacteriophage therapy.